2004
DOI: 10.1111/j.0742-2822.2004.03193.x
|View full text |Cite
|
Sign up to set email alerts
|

Live Three‐Dimensional Transthoracic Echocardiographic Assessment of Anomalous Origin of Left Coronary Artery from the Pulmonary Artery

Abstract: We describe live three-dimensional transthoracic echocardiographic (3DTTE) findings in a 52-year-old female who had previously undergone an aortopulmonary tunnel operation for anomalous origin of the left coronary artery (ACA) from the pulmonary artery. Three-dimensional transthoracic echocardiography clearly delineated the origin of the ACA from the posterolateral aspect of the main pulmonary artery just above the pulmonary valve, the surgically created tunnel, as well as a small defect in the tunnel near the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The use of 3D echo for the evaluation of coronary anomalies has been reported in only a handful of cases. Ilgenli et al have reported 3D imaging of an anomalous origin of the left coronary artery from the pulmonary artery in a 52‐year‐old patient 7 . Our patient's risk of sudden death was of great concern not only because of his coronary artery anomaly, which runs between the aorta and the pulmonary artery, but also because of the presence of the aneurysm and its propensity for thrombosis.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The use of 3D echo for the evaluation of coronary anomalies has been reported in only a handful of cases. Ilgenli et al have reported 3D imaging of an anomalous origin of the left coronary artery from the pulmonary artery in a 52‐year‐old patient 7 . Our patient's risk of sudden death was of great concern not only because of his coronary artery anomaly, which runs between the aorta and the pulmonary artery, but also because of the presence of the aneurysm and its propensity for thrombosis.…”
Section: Discussionmentioning
confidence: 66%
“…Ilgenli et al have reported 3D imaging of an anomalous origin of the left coronary artery from the pulmonary artery in a 52-year-old patient. 7 Our patient's risk of sudden death was of great concern not only because of his coronary artery anomaly, which runs between the aorta and the pulmonary artery, but also because of the presence of the aneurysm and its propensity for thrombosis. The technical aspects of 2D echocardiographic evaluation of this congenital coronary anomaly require a combination of imaging planes.…”
Section: Discussionmentioning
confidence: 98%
“…AO = aorta; RVOT = right ventricular outflow tract; RPA = right pulmonary artery. Reproduced with permission from Ilgenli et al . B. Coronary angiogram.…”
Section: Coronary Artery Anomaliesmentioning
confidence: 99%
“…Both transthoracic [18][19][20] and transesophageal [21,22, Three-dimensional echocardiography can also provide accurate depiction of the tricuspid valve from a surgical viewpoint from the right atrium [30 •• ], allowing the surgeon to make a more informed decision as to whether to repair the tricuspid valve.…”
Section: Structural Datamentioning
confidence: 99%